X-ray standing wave simulations based on Fourier vector analysis as a method to retrieve complex molecular adsorption geometries - Mercurio, Giuseppe; Maurer, Reinhard J.; Hagen, Sebastian; Leyssner, Felix; Meyer, Jörg; Tegeder, Petra; Soubatch, Sergey; Reuter, Karsten; Tautz, Frank Stefan (Frontiers in Physics, 2014)
We present an analysis method of normal incidence x-ray standing wave (NIXSW) data that allows detailed adsorption geometries of large and complex molecules to be retrieved. This method (Fourier vector analysis) is based on the comparison of both the coherence and phase of NIXSW data to NIXSW simulations of different molecular geometries as the relevant internal degrees of freedom are tuned. We introduce this analysis method using the prototypical molecular switch azobenzene (AB) adsorbed on the Ag(111) surface as a model system. The application of the Fourier vector analysis to AB/Ag(111) provides, on the one hand, detailed adsorption geometries including dihedral angles, and on the other hand, insights into the dynamics of molecules and their bonding to the metal substrate. This analysis scheme is generally applicable to any adsorbate, it is necessary for molecules with potentially large distortions, and will be particularly valuable for molecules whose distortion on adsorption can be mapped on a limited number of internal degrees of freedom.